Efectos de las technologias de punta en edicion e impresion de libros, revistas y prensa; cine radio y television (SELA CaracasVE, 1986)
Discusses integration of traditional and state-of-the-art technology and their effect on the mass media in Latin America. Synthesizes information on various technological innovations including the video-cassette, communication satelites, cable television, and informatics. Describes the combined effects of those technologies on the cultural industry and communications in Latin America. Recommends possible courses of action for SELA, inter-governmental and international organizations, the States of Latin America and other social agents of communication
Bibliography: p. 93-96